Targeting Bortezomib to Bone Increases Its Bone Anabolic Activity and Reduces Systemic Adverse Effects in Mice. (19th November 2019) - Wang, Hua; Zhang, Hengwei; Srinivasan, Venkat; Tao, Jianguo; Sun, Wen; Lin, Xi; Wu, Tao; Boyce, Brendan F; Ebetino, Frank H; Boeckman, Robert K; Xing, Lianping
ABSTRACT: Bortezomib (Btz) is a proteasome inhibitor approved by the FDA to treat multiple myeloma. It also increases bone volume by promoting osteoblast differentiation and inhibiting osteoclastogenesis in mice. However, Btz has severe systemic adverse effects, which would limit its use as a bone anabolic agent. Here, we designed and synthesized a bone‐targeted form of Btz by conjugating it to a bisphosphonate (BP) with no antiresorptive activity. We report that BP‐Btz inhibited osteoclast formation and bone resorption and stimulated osteoblast differentiation in vitro similar to Btz. In vivo, BP‐Btz increased bone volume more effectively than Btz in three mouse models: untreated wild‐type mice, mice with ovariectomy, and aged mice with tibial factures. Importantly, BP‐Btz had significantly less systemic side effects than Btz, including less thymic cell death, sympathetic nerve damage, and thrombocytopenia, and it improved survival rates in aged mice. Thus, BP‐Btz represents a novel anabolic agent to treat conditions, such as postmenopausal and age‐related bone loss. Bone targeting is an attractive approach to repurpose approved drugs to treat skeletal diseases. © 2019 American Society for Bone and Mineral Research. © 2019 American Society for Bone and Mineral Research.